1998
DOI: 10.1046/j.1365-3156.1998.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic quality in rural health centres in Burkina Faso

Abstract: Summary OBJECTIVETo study the quality of diagnostic practice in rural Burkina Faso. METHOD In 9 health centres of 3 districts, 313 outpatient consultations were observed, and 417 diagnoses by 15 nurses were analysed. Criteria for evaluation of patient history and clinical examination were based on the diagnostic guidelines distributed by the Ministry of Health. RESULTS In only 20% of the diagnoses the nurses took a sufficient history and in only 40% they conducted a sufficient clinical examination. In 21% pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
(11 reference statements)
3
25
0
Order By: Relevance
“…A study from Burkina Faso assessed the quality of diagnostic practice of nurses working in rural health centres. There was immense variation among nurses' skills of history taking and clinical examination and no correlation could be found with regard to their basic training (Krause et al, 1998b). This by no means suggests that training of health providers, especially as part of continuing education, is not essential.…”
Section: Discussionmentioning
confidence: 94%
“…A study from Burkina Faso assessed the quality of diagnostic practice of nurses working in rural health centres. There was immense variation among nurses' skills of history taking and clinical examination and no correlation could be found with regard to their basic training (Krause et al, 1998b). This by no means suggests that training of health providers, especially as part of continuing education, is not essential.…”
Section: Discussionmentioning
confidence: 94%
“…Possible reasons for low utilisation might be existing patients' dissatisfaction with the quality of health services [30,[34][35][36] leading to a preference towards traditional healers or self-treatment. Baltussen et al [37] found that the quality of care perceived at Nouna hospital was even worse than that of rural health centres.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent explanations are financial barriers and low quality of services [7]. Some elements of health care reforms in Burkina Faso address these issues, for instance by introducing quality management [8] and by implementing new financing mechanisms (e.g. community-based health insurances) [9,10].…”
Section: Introductionmentioning
confidence: 99%